Identifikasi Tren Warna Hijab Buttonscarves Tahun 2020 - 2022 - Irawati, Rahmita Annur; Ratuanissa, Tyar (Jurnal Desain Indonesia., 2026)
Color is used by humans in various aspects of life, including fashion products, interiors, marketing, and so on. Color is a visual element used mainly in business and marketing as a driving factor for consumers to purchase a product. The modest fashion industry used global color trends to adapt to its products. Using the right colors can have certain effects, such as in the modest fashion industry, especially hijabs, colors can increase product sales and keep up with the trends. Buttonscarves, one of the pioneers of motif hijab brands in Indonesia, has very diverse hijab colors and limited editions, so it is interesting to research. This research uses a quantitative method by collecting hijab color data, and then sorting the color palet previously collected by year using Adobe Illustrator tools. The sorting results are processed using AI to obtain annual color trends used by Buttonscarves. The findings obtained were that Buttonscarves used neutral and earth-tone color trends in 2020 and 2021, meanwhile, there were additional types of pastel colors in 2022. It is hoped that this research on Buttonscarves color trends can provide color trends insight for owners of similar industries to achieve the same success.